2023
DOI: 10.1021/jacs.3c01942
|View full text |Cite
|
Sign up to set email alerts
|

A Crystalline Monomeric Phosphaborene

Abstract: We report the synthesis of the monomeric phosphaborene Ar*P�B(TMP) (2) (Ar* = 2,6-bis(triisopropylphenyl)-3,5-diisopropylphenyl) containing 2-coordinate phosphorus and boron centers. Compound 2 has a PB bond length of 1.741(3) Å, the shortest reported to date. Computational examination of the bonding in 2 reveals, in addition to the σ bond, the presence of a single classical π bond and a large Wiberg bond index of 1.9707, consistent with double bond, and not triple bond, character. The chemistry of 2 is marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
(127 reference statements)
1
7
0
Order By: Relevance
“…Compounds 4 a and 4 b exhibit broad 31 P NMR signals at 4.0 ppm (ν 1/2 = 43.6 Hz) and 27.0 ppm (ν 1/2 = 43.8 Hz) in C 6 D 6 , respectively. In comparison to the free phosphaborenes (with 31 P NMR chemical shift of À 291.9 ppm for A and À 87.7 ppm for B), [8][9] these signals markedly shift to higher frequencies. Such shifts are lower in frequency than those noted for NHCstabilized P=B compounds (E-I, ranging between 57.3-192.9 ppm), highlighting the unique electronic effect of the NHB substituent on phosphorus.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Compounds 4 a and 4 b exhibit broad 31 P NMR signals at 4.0 ppm (ν 1/2 = 43.6 Hz) and 27.0 ppm (ν 1/2 = 43.8 Hz) in C 6 D 6 , respectively. In comparison to the free phosphaborenes (with 31 P NMR chemical shift of À 291.9 ppm for A and À 87.7 ppm for B), [8][9] these signals markedly shift to higher frequencies. Such shifts are lower in frequency than those noted for NHCstabilized P=B compounds (E-I, ranging between 57.3-192.9 ppm), highlighting the unique electronic effect of the NHB substituent on phosphorus.…”
Section: Resultsmentioning
confidence: 88%
“…These strategies temper either their donor or acceptor propensities, exemplified in compounds C-L (Figures 1b, 1c and 1d). [7] Notably, the landscape changed recently with the independent discoveries of two free phosphaborenes A [8] and B [9] by our group and Manners' group, respectively (Figure 1a). Both the steric protection from large substituents and the π-electron-donating character of the boron-attached nitrogen groups contribute to their stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…5 As a counter-strategy, it was later shown that protecting the boron atom by coordinating a bulky Lewis base was also viable. 6–9 Free phosphaborenes without further coordination could be isolated only very recently by utilizing substituents R and R′ that are either even more sterically demanding 10 or combine π-acceptor and π-donor capabilities in a kind of push–pull cooperation, in addition to their bulkiness (Scheme 1b). 9 However, extensive steric shielding also limits a possible application of phosphaborenes as further reagents.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, extensive steric shielding also limits a possible application of phosphaborenes as further reagents. 10,11 The design of substituents that balance stability and reactivity is therefore a current challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing heteroatoms, such as B, Si, N, S, and P atoms, into polycyclic aromatic hydrocarbons (PAHs) has emerged as an efficient strategy for modulating their chemical structures and optoelectronic properties. B←N Lewis pairs are easily constructed via electrophilic borylation, especially for electron-rich PAHs containing nitrogen atoms as anchors. , The energy of the B←N bond is 30 kcal/mol, which is strong enough to enhance the rigidity and planarity of PAHs. Replacing C–C bonds with isoelectronic B←N coordinate bonds is a versatile and simple method for tuning molecular structures, , solid-state packings, frontier orbitals, energy levels, and optoelectronic properties. Furthermore, strongly electron-deficient borylated N-heterocyclic PAHs can also possess lower LUMO levels and decreased HOMO–LUMO energy gaps, leading to red-shifts in absorption and emission. Despite the remarkable achievements in the synthesis of B←N Lewis pair-functionalized PAHs (Figure a), ,,, PAHs fused with multiple B←N Lewis pairs are still rare due to the lack of multidentate aromatic ligands capable of chelating several boron atoms in one system.…”
Section: Introductionmentioning
confidence: 99%